The Relationship between Students’ Speaking Skill and Students’ Self-Esteem of Mover F Class of NCL Madiun - Istyaning Asifa Dewi; Erlik Widiyani; Arri Kurniawan (Journal of English Teaching, 2022)
The purpose of this study is to know "The Relationship between Students' Speaking Skills and Students' Self-Esteem of NCL Madiun's Mover F Class." This study's problem formulation is whether there is a relationship between students' speaking skills and NCL Madiun's mover class students' self-esteem. The purpose of this study was to determine whether there was a relationship between students' speaking ability and self-esteem in the NCL Madiun mover class. Mover F class NCL Madiun students took part in this study. There are 180 students in the NCL Madiun Mover class, which is divided into ten classes. The purposeful sampling technique was used in this study, and the sample consisted of 19 students from Mover F class, with 12 boys and 9 girls. The type of data used is quantitative data. Data were gathered using speaking tests and self-esteem questionnaires. According to the findings, the average score for speaking skills was 73.53, while the average value for self-esteem was 72. Pearson's product-moment correlation produces 797 results and a sig value of less than 0.05, corresponding to 0.0001. The researcher comes to the conclusion that H1 is accepted and H0 is rejected, implying that there is a relationship between students' speaking abilities and self-esteem in the NCL Madiun Mover F class. Students who have high self-esteem outperform students who have low self-esteem.